PENGARUH PIJAT KAKI DAN PIJAT TELINGA TERHADAP TEKANAN DARAH PADA LANSIA YANG MENGALAMI HIPERTENSI - Hariati Hariati; Muthia Deliana; Dewi Pusparianda (BEST Journal (Biology Education, Sains and Technology), 2026)
Hypertension is a leading cause of death often referred to as the silent killer disease. Non-pharmacological approaches that can reduce hypertension are acupressure, Chinese herbs, herbal therapy, deep breathing relaxation, aromatherapy, classical music therapy, meditation and massage. The purpose of this study was to determine the Effect of Foot Massage Therapy and Ear Massage on Blood Pressure in Hypertension Patients. This study used a quasi-experimental design with One group pre-test and post-test design approach. The sampling technique used accidental sampling with a population of 851 respondents and a sample of 27 respondents. The results of the Wilcoxon test signed the comparison of blood pressure before and after giving foot massage therapy to respondents showed a significant change with p = 0.000 for systolic blood pressure and p = 0.000 for diastolic blood pressure (p